(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background: Hypertensive Heart Disease (HHD) is usually followed by cardiac remodeling. Different grades of Body Mass Index (BMI) also influence the cardiac structure. Hence, we evaluate the cardiac structure of HHD patients with various BMI grades. Materials and Method: This cross-sectional study involves 50 consecutive patients with HHD (hypertensive heart disease) from the Cardiology and Vascular Medicine Departement, Soetomo General Hospital Indonesia. Echocardiographic examination was done using GE vivid 7. Statistics were evaluated with SPSS 25.0. Results: The research showed that the grades of BMI (body mass index) was positively correlated with LA major (r=0.335), RA Major (r=0.371), LVD Mass (r=0.341), LVS Mass (r=0.303), LVPWD (r=0.369), LVPWS (r=0.391), and inversely correlated with LVSI Dopp (r=-0.376). Obese (BMI>30) patients have significantly lower ejection fraction compared to normoweight (BMI<25) patients (64.3±3.67% vs 62.12±0.98%, p=0.046). Conclusions: The grades of BMI in the HHD patient is associated with an increased volume of the left atrium and ventricle. This suggested that obese patient with HHD should be assessed carefully for atrial and ventricle enlargement.